Intelligent Tracking System For School Van - N.Swathi ,Ch.Padmaja,G.Navya Jyothi (International Journal of Advanced Science and Technology, 2020)
In this paper a system is introduced in which it is concentrated on the extent security of school van transportation system in our country. So the technology plays an important role for providing effectual solution by installing a communication network in the city. So, this paper introduces a system as an improvement to the available school van transport system in city – arrival time of school van is predicted by using GPS and Mobile Application technologies to establish a wireless network among home, stop and school in order to create this internetwork.G.Navya Jyothi